(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the history of developed countries shows that it is permissible to carry out measures aimed at improving the economy along with solving social issues. In our country, the principles of fair social policy, social agreement, solidarity, and inter-ethnic harmony were discussed. It was mentioned about the reforms implemented in the social sphere.